PENGARUH PENGGUNAAN FREKUENSI GELOMBANG BUNYI TERHADAP PERTUMBUHAN BENIH JAGUNG (Zea mays) DAN KACANG HIJAU (Vigna radiate) - Rahmaniah, Rahmaniah; Nurjannah, Nurjannah; L, Muh. Said (Teknosains: Media Informasi Sains dan Teknologi, 2017)
The research was conducted to determine the influence of usage frequency sound waves to grow seed corn and green beans. The method used in this study that the samples are given three types of treatment with the sound source given to this type of audiosonic frequency, ultrasonic and natural conditions. The results showed that the samples give growth response (height parameter of the plant, leaf width, leaf number and leaf length) are good as the samples treated with ultrasonic frequency of administration.